Office Social: Presentation Interactivity for Nearby Devices - Chattopadhyay, Debaleena; O'Hara, Kenton; Rintel, Sean; Radle, Roman (ACM - Association for Computing Machinery, 2016)
Slide presentations have long been stuck in a one-to-many paradigm, limiting audience engagement. Based on the concept of smartphone-based remote control of slide navigation, we present Office Social—a PowerPoint plugin and companion smartphone app that allows audience members qualified access to slides for personal review and, when the presenter enables it, public control over slide navigation. We studied the longitudinal use of Office Social across four meetings of a workgroup. We found that shared access and regulated control facilitated various forms of public and personal audience engagement. We discuss how enabling ad-hoc aggregation of co-proximate devices reduces ‘interaction costs’ and leads to both opportunities and challenges for presentation situations.